Mechanical Properties and Structure of the Hypereutectic Silumin Treated by an Electron Beam - Rygina M. E. Maria; Ivanov Yu. F. Yuriy Fedorovich; Laskovnev A. P. Alexander; Teresov A. D. Anton; Cherenda N. N. Nikolay Nikolaevich; Uglov V. V. Vladimir Vasilievich; Petrikova E. A. Elizaveta; Krysina O. V. Olga (2017, 2017)
Title screen